Not born a refugee woman : contesting identities, rethinking practices - Hajdukowski-Ahmed, Maroussia; Khanlou, Nazilla; Moussa, Helene, 1931- (Studies in forced migration, 2008)
Identity is constructed through a relational and contextual process informed by many factors - particularly gender. According to UNHCR, uprootedness caused by various forms of forced displacement affects about 37 to 40 million women and children in the world, posing major challenges to their identity and agency. Even though institutions and organizations have increasingly sought their participation, refugee women still find themselves in situations "where policies are generated, and programs delivered with little or no input from them" (Indra, 1989). This volume explores identity in all its co.